The poisoner's handbook: murder and the birth of forensic medicine in Jazz Age New York - Blum, Deborah (Penguin Press, 2010)
The untold story of how poison rocked Jazz Age New York City. A pair of forensic scientists began their trailblazing chemical detective work, fighting to end an era when untraceable poisons offered an easy path to the perfect crime. Chief medical examiner Charles Norris and toxicologist Alexander Gettler investigate a family mysteriously stricken bald, factory workers with crumbling bones, a diner serving poisoned pies, and many others. Each case presents a deadly new puzzle and Norris and Gettler create revolutionary experiments to tease out even the wiliest compounds from human tissue. From the vantage of their laboratory it also becomes clear that murderers aren't the only toxic threat--modern life has created a kind of poison playground, and danger lurks around every corner